Determinants of male involvement in partner’s cervical cancer screening in Makueni County, Kenya - Wambua, Ruth T.; Onsongo, Lister N.; Ndombi, Eric M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Cervical cancer is the fourth cause of cancer deaths globally and is ranked in Kenya as the second cause of cancer-related deaths among females. Men are crucial in minimizing cervical cancer burden. This study sought to establish the socio-cultural and economic factors determining male involvement in their partner’s cervical cancer screening in Makueni County, Kenya. Methods: A mixed-method cross-sectional study was used to obtain quantitative and qualitative data from men using questionnaires. Participants were married men aged 18-64 who sought services at three mid-level rural hospitals in Makueni County. Three key Informant face-to-face interviews were conducted. Quantitative data were analyzed using descriptive statistics and inferences. Qualitative data was analyzed through codes and themes. Results: The study included 291 men. Men’s involvement in their partner’s cervical cancer screening was low. Only 18% of the participants showed high involvement. The participants’ mean age was 38.59 (SD±10.51). Younger men (median age=33 years) were significantly more involved than their older counterparts (median age=38 years) (U=4363, p=0.020). The level of male involvement was strongly linked to the rural area of residence (p=0.001) and the hospital where the respondents were interviewed (p=0.012). Other determining factors included employment status (p=0.004), educational level (p=0.000, and spousal screening history (p=0.000). The odds of male involvement were higher in men who understood their role in cervical cancer screening than those who did not (OR=4.550, 95% CI [1.307, 15.844], p=0.017). Conclusions: Male involvement in their partner’s cervical cancer screening remains significantly low, and demographics and sociocultural factors are key to these poor trends.